The problem of tobacco use among students of Lublin universities - Piotr Książek; Piotr Dreher; Sylwia Mojsym-Korybska; Kinga Grabska-Kusiak; Andrzej Wójcik; Mirosław Pucek (Kazimierz Wielki University, 2019)
Introduction. As for operational purposes concerning risk factors and activities in health promotion of the National Health Program, one should find the point of talking about reducing the prevalence of smoking. The main characteristics of tobacco dependence are: inability to stop smoking or significantly reducing it, the emergence of withdrawal syndrome caused by smoking cessation, persistent intake of tobacco, even when serious illness should prompt discontinuation. Aim. The aim of the research conducted among the students of Lublin universities was to identify the level of nicotine use by young people, to find out socio-demographic components of these behaviours and to determine the need for preventive activities in the field of cigarette smoking Meterial and methods. Studies were carried out among full-time students of all the public universities in Lublin: the Medical University (MU), the Maria Curie-Skłodowska University (MCSU), University of Life Sciences (ULS), the John Paul II Catholic University of Lublin (CUL), Technical University of Lublin (TUL). Results.The study shows that 75% of students do not smoke cigarettes at all, while among smokers - 12% smoke regularly and 13% occasionally. We noticed a very interesting relationship - it turned out that women smoke more than men and are more likely to declare regular smoking. Also interesting is the fact that people living while studying in the family home and having parents with higher education smoke more. Conclusions.Nicotine smoking is a serious problem among students of Lublin universities.